The relationship between emotional intelligence and high risk sexual behaviors in women referring to central unit of forensic medicine in Tehran - Daneh Far, Zahra; Ahmadi, Mahboobeh; Alavi Majd, Hamid; saberi, Mahdi (Advances in Nursing & Midwifery, 2016)
Background and Aim: In all over the world, sexual activities are increasing among single youth. Personality as a determining factor can influence all human personal and social behaviors. Studies show that some Personality traits may contribute to high-risk sexual behaviors. The aim of the current study was the assessment of correlation between high risk sexual behaviors and emotional intelligence. Materials and Methods: This is a descriptive study with non-probability and convenience sampling method. The samples of research were girls and women 65 years-old with high-risk sexual behaviors that were referred to a female forensic unit in Tehran in 2014. The research instruments included a researcher-made questionnaire to assess high risk sexual behaviors and Bar-on emotional intelligence questionnaire. The validity of high risk sexual behavior questionnaire was determined using the content validity index and content validity ratio. The test-retest method was selected to determine the reliability and stability of high-risk sexual behavior questionnaires. Then, Interrater reliability was determined by the kappa coefficient. The questioner had a suitable level of reliability. Data analysis was performed using Pearson and Spearman correlation coefficients, logistic regression and independent T test. Results: The most frequent sexual behavior was vaginal sex. Regression analysis showed that there were negative correlations between vaginal intercourse with happiness and self‐actualization as some emotional intelligence components. there were also negative correlations between oral sex with problem solving, self‐actualization, realism, stress tolerance and independence as other emotional intelligence components (p<0/05). There is only a significant positive correlation between empathy component of emotional intelligence and vaginal intercourse (p<0/05). Discussion and conclusions: The results support of the impact of emotional intelligence and its components on high-risk sexual behaviors among girls and women. Key words: Emotional Intelligence; Sexual Behavior; Forensic Medicine